The Chemical Bond III 100 years old and getting stronger - Mingos, D. Michael P. (Structure and Bonding, 2017)
Christopher B. Caputo and Douglas W. Stephan--Non-conventional Lewis Acids and Bases in Frustrated Lewis Pair Chemistry Andreas Phanopoulos, Nicholas J. Long, and Philip W. Miller--Triphosphine Ligands: Coordination Chemistry and Recent Catalytic Applications Robert H. Crabtree--Sigma Bonds as Ligand Donor Groups in Transition Metal Complexes Malcolm L.H. Green and Gerard Parkin--The Covalent Bond Classification Method and Its Application to Compounds That Feature 3-Center 2-Electron Bonds Ghenwa Bouhadir, Didier Bourissou--Coordination of Lewis Acids to Transition Metals:Z-Type Ligands.